Anmeldelser - Müller, Mette (Danish Yearbook of Musicology, 1981)
Review of: Folkmusikboken. Jan Ling (red.), Gunnar Ternhag (red.), Anna Johnson, Marta Ramsten (red.), Birgit Kjellstram, Rigmor Sylven, Gunnar Ermedahl, Ann-Marie Ohlsson, Ville Roempke, Ingmar Bengtsson. Bokförlaget Prisma, Stockholm 1980,